Secrets from the GPU: True random bit generation and faster Diffie–Hellman for systemic cryptography - Mahé, Eric; Chauvet, Jean-Marie (Journal of computer virology and hacking techniques, 2014)
In the current controversial context caused by the disclosure of classified details of several top-secret United States and British government mass surveillance programs to the press by former NSA contractor Edward Snowden, issues of data privacy, anonymity, unlinkability, forward secrecy and deniability have raised to public prominence. In this work we investigate how an alternate usage of state-of-the-art yet ubiquitous computing platforms might help sovereign, citizen and general public recovery of control over privacy. These goals are notoriously difficult to achieve on the Internet today due to the insufficient public-key infrastructure at the user level. Our approach leverages modern multi-core processors and general-purpose computing on graphics processing units, both as a source of true random entropy pools and computational engines for very fast elliptic curve cryptography (ECC). Such autonomous, high-frequency Diffie–Hellman-ready agents reside in a breadth of devices ranging from smartphones and tablets, to laptops and high-end servers in datacenters. In contrast to the current circumstance, this suggested infrastructure enables generalized symmetric exchanges with the Vernam cipher without compromising ease-of-use nor requiring revolutionary changes in today’s well-grounded ECC theory.